Isolation and chemical Investigation of Bioactive Saponin from Tridex procambens for Antiasthmatic Activity - NAGINA, HIRDESH; PATEL, MAMTA; JAIN, D.K.; SAXENA, R.C. (Asian Journal of Chemistry, 2010)
Tridex procombens is a terrestrial weeds, widely distributed in tropical climate. This plant yields saponin like compound. Flavone glucoside 5,3',4'-trihydrory-7,5'-dimethoxy-5-O-α-L-methyl pyranoside, which have shown antiasth-matic activity both in water as well as in alcoholic extract. Maximum mast cell degranulation activity was noted as 100 mg/kg body weight dose causing 67 % inhibition decreasing mast cell activity.